Uganda : Background Paper. (IMF Staff Country Reports; Country Report ;, 1995)
This Background Paper presents a long-term perspective on investment and output performance in Uganda, beginning after the country gained independence in the early 1960s. Against the background of long-term trends in savings, investment, and output, the paper describes the initial conditions that led to the adoption of adjustment policies. The macroeconomic policy mix, together with important structural policies, is analyzed and the outcomes are assessed for 1987-94, during which Uganda pursued an ongoing adjustment program supported by successive arrangements with the IMF under the structural adjustment facility and the enhanced structural adjustment facility.